2018
DOI: 10.1063/1.5028204
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of thermochemically non-equilibrium inductively coupled plasmas under different operating parameters

Abstract: A thermochemical non-equilibrium model for inductively coupled plasmas (ICPs) has been utilized to investigate the effect of different operating parameters. The effects of operating parameters, including the injection mass flow rate, input power, operating pressure, and induction frequency, are studied in this manuscript. The spatial distributions of electron temperature, plasma velocity, and chemical particles fields are discussed under different operating conditions. The simulation results show that the spat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…To check the correctness of the velocity simulated in our study, we consult several relevant references. [12,25,42] Approximate values of the simulated velocity are found for the high power ICPs. [25,42] For example, Vasil'evskii and Kolesnikov [25] simulated an air ICP flow under similar working conditions: the nominal input power P = 90 kW, f = 0.44 MHz, p = 10 kPa, m = 2.8 g/s.…”
Section: Numerical Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…To check the correctness of the velocity simulated in our study, we consult several relevant references. [12,25,42] Approximate values of the simulated velocity are found for the high power ICPs. [25,42] For example, Vasil'evskii and Kolesnikov [25] simulated an air ICP flow under similar working conditions: the nominal input power P = 90 kW, f = 0.44 MHz, p = 10 kPa, m = 2.8 g/s.…”
Section: Numerical Resultsmentioning
confidence: 93%
“…[25] Although their input power is lower than P = 160 kW in our case 1, their working pressure and mass flow rate are also lower than p = 15 kPa, m = 16 g/s in case 1, respectively. Lu and Feng [12] has reported that the plasma velocity decreases as the pressure and the mass flow rate increase. Thus, for case 1 the simulated maximum velocity (110 m/s) has the same order of magnitude as the one (150 m/s) reported by Vasil'evskii and Kolesnikov.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 1 more Smart Citation